Realization of Constitutional Norms on Accessibility and Quality of Education in the Russian Federation as a Social State - Ilyich Skuratov, Yurij; Yurievich Nikodimov, Igor; Gerasimovich Pavlikov, Sergey; Nikolaevich Prudnikov, Mikhail (International Journal of Engineering and Technology, 2018)
The article is devoted to the problems of increasing the effectiveness of the realization of constitutional norms on the accessibility and quality of education in the Russian Federation as a social state. The basis of relevant scientific discussions is the search for the best directions in the realization of the norms of the Constitution of Russia, which in Art. 43 fixes the right to education (part 1), guarantees "the general accessibility and free of preschool, basic general education and secondary vocational education in state or municipal educational institutions and enterprises" (Part 2), fixes the possibility "to receive free higher education in the state or municipal educational institution and at the enterprise on a competitive base "(part 3). The authors of the article attempt to substantiate the relevance of the objective identification of the evaluation of educational activity on the part of: the scientific community (primarily as a constitutional value); trainees (their legal representatives), potential trainees and teaching staff - in the part of systematic improvement of its legal regulation.